Hypertension and early menopause after the use of assisted reproductive technologies in women aged 43 years or older: Long‐term follow‐up study. Issue 12 (8th October 2016) - Rosato, Elena; Perrone, Giuseppina; Capri, Oriana; Galoppi, Paola; Candelieri, Miriam; Marcoccia, Eleonora; Schiavi, Michele Carlo; Zannini, Ilaria; Brunelli, Roberto
Abstract: Aim: The aim of this study was to investigate the long‐term consequences to women's health and the onset of menopause in healthy women of advanced reproductive age who conceived by assisted reproductive technologies (ART). Methods: Healthy women who conceived by ART (72) and controls (80) were selected among 320 women ≥ 43 years, who delivered between January 2010 and December 2011 in the Department of Gynecological and Obstetrical Sciences and Urological Sciences of "Sapienza" University of Rome. Body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), and presence of hypertension and diabetes were analyzed at three days, six months, and three years after delivery. The onset of menopause was analyzed after three years. Results: In the ART group, SBP, DBP and hypertension were higher at three days, six months, and three years after delivery. Menopausal age was significantly lower. Conclusion: The impact of ART in healthy women of advanced reproductive age in the years after delivery is not limited to the possible development of cardiovascular risk factors, such as hypertension, but can also influence the age of onset of menopause.